ALTRUISME (AL-ISAR) DALAM PERSPEKTIF AL-QUR’AN - Siti Fatimah (IAT IAIN Pontianak, 2021)
Abstract This article discusses about a term that is called by altruism. Altruism is a willingness to do something that bring advantages to others sincerely. In the Quran surah al-Hasr verse: 9, this term is known as al-Isar. The Existence of altruism or al-Isar in social life is very important and necessary. It is because people are social beings that always need the presence of other people in their daily life. The method of this research is library research and thematic vocabulary. It is concluded that altruism is phenomenal social events in Islam because it is a behaviour that puts others first even though he is in troubles. Altruism has no limit generally, so that it becomes top of brotherhood.